Lessons learnt from implementing the Good Governance for Medicines Programme in Zimbabwe - Charles Chiedza Maponga; Takudzwa Chikwinya; Ropa Hove; Newman Madzikwa; Fine Mazambara; Stanley M Midzi; Forward Mudzimu; Misheck Ndlovu; William Ngirande; Ndanatseyi Vengesayi; Alison T Mhazo (BMJ Global Health, 2022)
WHO launched the Good Governance for Medicines (GGM) programme in 2004 with the aim of fighting the problem of corruption in the pharmaceutical sector. Zimbabwe adopted the GGM programme in 2015 and developed its own implementation framework (GGM-IF) in 2017 based on the WHO global guidelines and recommendations. Zimbabwe’s GGM-IF emerged from; (1) home-based expertise, (2) extensive local consultations and (3) effective incorporation into existing institutions. The GGM-IF committed to implementing a focused programme over a 5-year period from 2017 to 2022 with the expressed goal of improving transparency and accountability in the pharmaceutical sector as a key enabler to improve access to medicines. Midway through its projected lifespan, some notable achievements materialised attributed to key success drivers, including mutual collaboration with the Ministry of Health and Child Care’s existing Global Fund supported Quality Assurance Programme. Key challenges faced include limited funding for the programme, a shifting policy environment driven by a political transition and reorientation of priorities in the wake of the COVID-19 pandemic. This manuscript articulates 3-year operationalisation of Zimbabwe’s GGM-IF highlighting the success drivers, implementation challenges and lessons learnt.